Is Extra Virgin Olive Oil an Ally for Women's and Men's Cardiovascular Health?. (27th April 2020) - Franconi, Flavia; Campesi, Ilaria; Romani, Annalisa
Abstract : Noncommunicable diseases are long-lasting and slowly progressive and are the leading causes of death and disability. They include cardiovascular diseases (CVD) and diabetes mellitus (DM) that are rising worldwide, with CVD being the leading cause of death in developed countries. Thus, there is a need to find new preventive and therapeutic approaches. Polyphenols seem to have cardioprotective properties; among them, polyphenols and/or minor polar compounds of extra virgin olive oil (EVOO) are attracting special interest. In consideration of numerous sex differences present in CVD and DM, in this narrative review, we applied "gender glasses." Globally, it emerges that olive oil and its derivatives exert some anti-inflammatory and antioxidant effects, modulate glucose metabolism, and ameliorate endothelial dysfunction. However, as in prescription drugs, also in this case there is an important gender bias because the majority of the preclinical studies are performed on male animals, and the sex of donors of cells is not often known; thus a sex/gender bias characterizes preclinical research. There are numerous clinical studies that seem to suggest the benefits of EVOO and its derivatives in CVD; however, these studies have numerous limitations, presenting also a considerable heterogeneity across the interventions. Among limitations, one of the most relevant in the era of personalized medicine, is the non-attention versus women that are few and, also when they are enrolled, sex analysis is lacking. Therefore, in our opinion, it is time to perform more long, extensive and lessheterogeneous trials enrolling both women and men.